Collisional excitation in reactive systems: recent advances in modeling molecular processes for astrochemistry - Pirlot Jankowiak, Paul (Frontiers in Astronomy and Space Sciences, 2025)
Collisional excitation in reactive systems plays a central role in astrochemistry. Accurate state-to-state rate coefficients are key parameter for the determination of excitation conditions of interstellar molecules with the most abundant species in space (H, He and H2) through collisions. Unfortunately, reliable data for collisions involving interstellar reactive radicals and ions are scarce. Despite the molecular simplicity of these systems, considering the competition between nonreactive and reactive processes on equal footing remains a true theoretical and computational challenge in particular for bimolecular reactions, in addition to excitation processes in open-shell species. This minireview emphasizes recent progress in theoretical approaches for state-to-state scattering in reactive systems of astrochemical interest. We discuss the strengths and limitations of state-of-the-art quantum methods on collisions involving direct and indirect reactions; and the encouraging alternatives proposed by statistical frameworks. We highlight the impact of the computed state-to-state rate coefficients in astrophysical modeling.